Mengembangkan Kreativitas Anak Usia Dini Melalui Pemanfaatan Media Barang Bekas - Siti Kholilah (PG-PAUD Trunojoyo, 2016)
This study aims to improve children's creativity through the use of media used goods. This research was conducted in kindergarten Miftakhul Ulum in group B, with the number of students 13 children. This study uses classroom action research using the design study model of Kurt Lewin. This research was conducted in two cycles with each cycle comprising 4 meeting. An increase in overall child creativity in pratindakan with a percentage of 31%. Percentage in the first cycle was 43.08%, while the percentage in the second cycle is 82.46%. So it can be concluded that the media used goods can improve a child's creativity TK B Miftakhul Ulum in the learning process.